The Fab Fragment of a Human Anti-Siglec-9 Monoclonal Antibody Suppresses LPS-Induced Inflammatory Responses in Human Macrophages - Chu, Sasa; Zhu, Xuhui; You, Na; Zhang, Wei; Zheng, Feng; Cai, Binggang; Zhou, Tingting; Wang, Yiwen; Sun, Qiannan; Yang, Zhiguo; Zhang, Xin; Wang, Changjun; et al. (Frontiers in Immunology, 2016)
Sepsis is a major cause of death for hospitalized patients and is characterized by massive overreaction of immune responses to invading pathogens which is mediated by cytokines. For decades, there has been no effective treatment for sepsis. Sialic acid-binding, Ig-like lectin-9 (Siglec-9), is an immunomodulatory receptor expressed primarily on hematopoietic cells which is involved in various aspects of inflammatory responses and is a potential target for treatment of sepsis. The aim of the present study was to develop a human anti-Siglec-9 Fab fragment, which was named hS9-Fab03 and investigate its immune activity in human macrophages. We began by constructing the hS9-Fab03 prokaryotic expression vector from human antibody library and phage display. Then, we utilized a multitude of assays, including SDS-PAGE, Western blotting, ELISA, affinity, and kinetics assay to evaluate the binding affinity and specificity of hS9-Fab03. Results demonstrated that hS9-Fab03 specifically bind to Siglec-9 antigen with high affinity, and pretreatment with hS9-Fab03 could attenuate lipopolysaccharide (LPS)-induced TNF-α, IL-6, IL-1β, IL-8, and IFN-β production in human PBMC-derived macrophages, but slightly increased IL-10 production in an early time point. We also observed similar results in human THP-1-differentiated macrophages. Collectively, we prepared the hS9-Fab03 with efficient activity for blocking LPS-induced pro-inflammatory cytokines production in human macrophages. These results indicated that ligation of Siglec-9 with hS9-Fab03 might be a novel anti-inflammatory therapeutic strategy for sepsis.